Faktor yang Mempengaruhi Kepuasan Kunjungan Wisatawan Pantai Pasir Padi Kota Pangkalpinang - Fadiah Izzah Ajrina; Divina Aufa Widiana; Nada Yuliana Rahma; Yoan Dian Perdana (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The tourism sector is one of the strategic sectors in Indonesia's development, as mandated by Law Number 10 of 2009. Pangkalpinang City, the capital of Bangka Belitung Islands Province, holds significant potential for developing marine tourism, such as Pasir Padi Beach. This area is designated as a Provincial Tourism Strategic Area (KSPP) based on Regional Regulation Number 7 of 2016. Despite its attractions and strategic location, the development of this area must prioritize environmental sustainability and optimize factors influencing tourist satisfaction, such as facilities, pricing, and tourist attractions. This study aims to analyze the relationship between tourist satisfaction and revisit intention to Pasir Padi Beach. Using a quantitative approach, data were collected through surveys using questionnaires and then analyzed with SPSS software. The measured variables include tourism facilities consisting of accommodation, restaurants, and information centers; pricing, which includes affordability, appropriateness, and price competitiveness; as well as tourist attractions, which consist of natural beauty, activities, and cleanliness. The findings reveal that natural beauty, ticket price affordability, cleanliness at the tourist site, the quality of homestays, and the quality of restaurants and street vendors significantly influence tourist satisfaction. By identifying the factors that influence tourist visits, the government can develop appropriate strategies and formulate policies to increase tourist arrivals, based on the key factors that significantly affect tourist satisfaction through their intention to revisit.